PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS KEMITRAAN (Studi Kasus Nelayan Desa Sulamu Kabupaten Kupang NTT) - samadara, selfesina (BISNIS, 2016)
Less development of the fisheries sector and its contribution to the PAD, especially traditional fishery business in the village Sulamu predominantly due to the lack of capital. The research objectives: 1) To describe the socio-economic conditions of the fishing village of Sulamu, Kupang. 2) To find a model of partnership in addressing the problem of poverty in the fishing village Sulamu Kupang district. Methods of data collection using survey method, observation method, and the quantitative and qualitative methods. The sampling method using purposive sampling method. Data presented in the form of tabulation and then analyzed descriptively, which results or capital investment, total cost, revenue, and profit in order to obtain the level of welfare of traditional fishermen in the village Sulamu. Analysis of the performance of the economy as acriterion indicates that the undiscounted net gillnet fisheries inthe village Sulamu profitable, efficient and feasible to operate with R / C ratio of 1.35 and profitability of 35.39% and a payback period (PP) of 2.8.